editorial - Zia, Rashid (Pakistan Journal of Ophthalmology, 2020)
Glaucoma, is a group of conditions characterized by optic disc cupping and visual field defects. Evaluation, staging and monitoring of glaucoma requires a series of functional tests which is a time consuming process. So far, Standard Automated Perimetry (SAP) is recognized as a reference standard for all the functional testing1. Glaucoma may present with a structural or a functional change. Therefore, the correct test strategy for diagnosis is vital to prevent overlooking the onset of glaucoma2.